Profiling Language Assessment Over the Last Half A Century: A Review of Talking About Language Assessment: The LAQ Interviews. Issue 3 (2nd July 2016) - Zheng, Yujing; Gu, Xiangdong
ABSTRACT: Talking About Language Assessment: The LAQ Interviews, edited by Antony John Kunnan, is a collection of 12 interviews with the leading researchers from the area of language assessment and related fields (John B. Carroll, Merrill Swain, Alan Davies, John Trim, Barnard Spolsky, Kenji Ohtomo, Charles Stansfield, Elana Shohamy, Gui Shichun, Lyle F. Bachman, J. Charles Alderson, and Liz Hamp-Lyons) originally featured in Language Assessment Quarterly (2004–2014). With oral accounts and reflections on such key issues as language ability, assessment development, validation argument, test use and impact, and language assessment policy, the volume profiles the research and practice of language assessment over the last half a century from historical, theoretical, methodological, and social perspectives. It reveals a significant shift of research focus from technical considerations to social dimensions in language assessment over the last half a century. Through "expanding the coverage of genre" into discursive dialogues, the book manifests how personal background, formative experience, and academic accomplishments contribute to the development and professionalization of language assessment. The book might be further improved with the interviews reorganized and grouped under the same section headings, some up-to-date issues discussed in depth, and some irrelevant information edited out.